Sejarah Kegiatan Fatwa pada Era Al-Tabi’in - Abd. Rahman, Noor Naemah (Jurnal Usuluddin, 2002)
Historically, as far as the fatwa activities were concerned, many scholars noticed that several developments had occurred during the tabi’in period, compared to the previous period, i.e. the sahabah period. Obviously, such development took place mainly due to the changing situation of the political, cultural, intellectual activities besides other factors. This article tries to outline such changing realities and their effect upon the practice of fatwa during the tabi’in time.